2014
DOI: 10.4172/2157-7560.1000242
|View full text |Cite
|
Sign up to set email alerts
|

Grouping Pig-Specific Responses to Mitogen with Similar Responder Animals may Facilitate the Interpretation of Results Obtained in an Out-Bred Animal Model

Abstract: Pig peripheral blood-derived mononuclear cells (PBMCs) and lamina propria mononuclear cells (LPMCs) stimulated with mitogens ex vivo can show significant animal-to-animal variation lead to difficulty in interpreting responses in an out-bred animal species. Mixed-cell populations were stimulated ex vivo with 2.5 μg/ml Con A or 2.5 ng/ml PMA plus 250 ng/ml ionomycin (PMAi; (LPCMs only)) or media alone for 72 hours. Supernatants were then tested for cytokine production using a Bioplex assay for porcine IFNα, IFNγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…On the other hand, the comparatively low expression levels of IL-10 in PBMCs of both the breeds depict an overall control of the T H 1 and T H 2 response preventing the possibility of aberrant adaptive immune response. Earlier studies indicated that the cytokine production and T H 1/T H 2 ratios are highly variable between and within pig breeds (Pasternak et al 2014). Importantly, this study revealed that the T H 1 response of Zovawk pigs in terms of mRNA expression of IL-2 and IFN-c was much higher than the mRNA expression of those of LWY pigs.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…On the other hand, the comparatively low expression levels of IL-10 in PBMCs of both the breeds depict an overall control of the T H 1 and T H 2 response preventing the possibility of aberrant adaptive immune response. Earlier studies indicated that the cytokine production and T H 1/T H 2 ratios are highly variable between and within pig breeds (Pasternak et al 2014). Importantly, this study revealed that the T H 1 response of Zovawk pigs in terms of mRNA expression of IL-2 and IFN-c was much higher than the mRNA expression of those of LWY pigs.…”
Section: Discussionmentioning
confidence: 49%
“…Earlier studies indicated that the cytokine production and T H 1/T H 2 ratios are highly variable between and within pig breeds (Pasternak et al . ). Importantly, this study revealed that the T H 1 response of Zovawk pigs in terms of mRNA expression of IL‐2 and IFN‐γ was much higher than the mRNA expression of those of LWY pigs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations